Optimalisasi Bumdes: Meningkatkan Profesionalisme Pengurus Untuk Pembangunan Desa Berkelanjutan - Saepulloh, Agus; Rafles, Rafles (Syntax Literate, 2025)
The development of the rural economy through Village-Owned Enterprises (BUMDes) has been initiated by the government, but its effectiveness is still limited. In Banyuasin Regency, out of 249 BUMDes, only 37 are legal entities, including BUMDes Mulia Asri in Mulya Sari Village, Tanjung Lago District. Unfortunately, BUMDes Mulia Asri has experienced operational problems since its establishment in 2017, although it is expected to improve the village's economy through agriculture, plantations, and trade businesses. Some of the main problems identified are low human resource capacity, lack of financial recording guidance, and lack of necessary training. The majority of Mulia Asri BUMDes administrators are only high school graduates and have limited understanding of BUMDes institutions. In addition, the capital distribution model from the village government has not been optimal, hampering the performance of BUMDes. To overcome this problem, it is necessary to increase the capacity and competence of BUMDes administrators through mentoring by involving village assistants and the provision of modules and independent teaching materials by the Ministry of Villages and can be accessed online. Collaborative support from the village government is crucial in improving the performance of BUMDes. With the right solution, BUMDes Mulia Asri is expected to contribute significantly to the village economy, increasing Village Original Income (PAD Desa).